PELAKSANAAN AKAD KAFÄ€LAH BIL UJRAH PADA PRODUK PEMBIAYAAN MULTIJASA BTN IB DI PT. BANK TABUNGAN NEGARA (BTN) KCPS SURAPATI CORE BANDUNG MENURUT HUKUM EKONOMI SYARIAH - Marliananingsih, Sari (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACTMultilateral financing BTN iB is one of the products of Bank BTN Syariah which provides solutions for customers who can be used to fund various services by using kafÄlah contract which is accompanied by ujrah. The term defined in multilateral financing shall be in accordance with the DSN No.44 / DSN-MUI / VII / 2004 fatwa on multi-service financing that a large ujrah or fee must be agreed at the beginning of the contract and expressed in nominal form not in percentage terms. This study aims to determine: 1) Implementation of multijasa financing BTN iB in Bank BTN KCPS Surapati Core Bandung. 2) Bank policy in determining ujrah on multi-service financing BTN iB Bank BTN KCPS Surapati Core Bandung. 3) Review of sharia economic law against multi-service BTN iB BTN KCPS Surapati Core Bandung in relation to the fatwa of DSN-MUI fatwa NO: 11 / DSN-MUI / IV / 2000 About KafÄlah. KafÄlah is a guarantee given by the insurer (kafÄ«l) to a third party (makfÅ«l lah) to fulfill the obligation of the second party or the borne (makfÅ«l 'anhu). In the fatwa of the National Shari'a Council No.44 / DSN-MUI / VII / 2004 on multilateral financing states that its legal multijasa financing is allowed (jÄiz) by means of ijÄrah or kafÄlah contracts, and if the kafÄlah contract is used it must follow all existing provisions in the fatwa of kafÄlah. And in the fatwa mentioned that big ujrah or fee must be agreed at the beginning of the contract and expressed in nominal form not in percentage form. The method used in this research is using descriptive method, that is method describing the implementation of multijasa BTN iB with qualitative data type and analyzed by using primary data source and secondary data through observation, interview and literature study. The results of this study indicate that: 1) Bank BTN KCPS Surapati Core on the implementation of multi-service financing BTN iB acts as a guarantor of services organized by third parties to meet customer obligations, for these benefits customers must pay ujrah according to agreement, 2) The concept of ujrah determination shall be determined by Bank BTN KCPS Surapati Core based on a Circular Letter of the Board of Directors issued by the head office of the State Savings Bank Syariah. Determination ujrah in multijasa financing BTN iB using ujrah determination method in the form of percentage. 3) In the Fatwa of the National Shari'a Council No.44 / DSN-MUI / VII / 2004 on multilateral financing which states that a large ujrah or fee must be agreed at the beginning of the contract and expressed in nominal form not in percentage form and in the execution of Bank BTN KCPS Surapati Core in addition to telling the form ujrah in the percentage of banks were attached in a nominal form to avoid gharar or obscurity for customers.